2023
DOI: 10.1111/bjh.19009
|View full text |Cite
|
Sign up to set email alerts
|

Fetal and neonatal alloimmune thrombocytopenia: No evidence of systemic inflammation as a modulator of disease severity. Could placental inflammation be key?

Abstract: SummaryIn fetal/neonatal alloimmune thrombocytopenia (FNAIT), maternal alloantibodies against paternal human platelet antigens (HPA) cross the placenta and lead to platelet destruction. The extent of thrombocytopenia varies among neonates, and inflammation may constitute an important trigger. A set of stable inflammatory markers was measured in serum samples from neonates with low platelet counts, of which n = 50 were diagnosed with FNAIT due to anti‐HPA‐1a antibodies and n = 50 were thrombocytopenic without d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…A recent large study of newborns with FNAIT showed that some babies, especially males again, were small 23 . A separate study in FNAIT concluded, after exploration of levels of procalcitonin, sFlt1, and CD14, that placental rather than systemic inflammation appeared to modulate the severity of FNAIT 24 . One way to synthesize this information is that anti‐HPA‐1a in FNAIT binds to HPA‐1a expressed on syncytiotrophoblasts from the fetal part of the placenta causing villitis, which may in turn result in smaller babies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent large study of newborns with FNAIT showed that some babies, especially males again, were small 23 . A separate study in FNAIT concluded, after exploration of levels of procalcitonin, sFlt1, and CD14, that placental rather than systemic inflammation appeared to modulate the severity of FNAIT 24 . One way to synthesize this information is that anti‐HPA‐1a in FNAIT binds to HPA‐1a expressed on syncytiotrophoblasts from the fetal part of the placenta causing villitis, which may in turn result in smaller babies.…”
Section: Discussionmentioning
confidence: 99%
“…23 A separate study in FNAIT concluded, after exploration of levels of procalcitonin, sFlt1, and CD14, that placental rather than systemic inflammation appeared to modulate the severity of FNAIT. 24 One way to synthesize this information is that anti-HPA-1a in FNAIT binds to HPA-1a expressed on syncytiotrophoblasts from the fetal part of the placenta causing villitis, which may in turn result in smaller babies. Marked placental inflammation has been found in, for exam-ple, preeclampsia to result in smaller babies.…”
Section: F I G U R Ementioning
confidence: 99%